Tiroler Geotechniktag 2022 Naturgefahren - Hofmann, Robert (Geotechnik und Naturgefahren, 2023)
The sustainable protection against natural hazards, the prevention of damage in settlement areas and in infrastructure buildings, the assessment of dynamic process effects and the interaction with the soil properties characterize the research focus of the Unit of Geotechnical Engineering. Protective dams, torrent barriers, rockfall and avalanche protection or the securing of landslides are the subject of current research projects.